Assessment of Safe Loading Conditions for the SPCB Deck Crane Using Hydrostatic and GZ Curve Analysis - Santoso, Budhi; Romadhoni, Romadhoni -; Nasution, Polaris; Hardiyanto, Hardiyanto; Ariany, Zulfaidah (Institut Teknologi Sepuluh Nopember, 2025)
This study comprehensively assesses safe loading conditions for the Self-Propelled Crane Barge (SPCB) Deck Crane by integrating detailed hydrostatic calculations with righting-arm (GZ) curve analysis. At the designated summer draft of 2.75 m, baseline parameters—displacement (1 716 t), centre of buoyancy (KB = 0.765 m), transverse metacentre (KM = 2.780 m), and metacentric height (GM = 1.23 m)—were established from the vessel’s stability booklet. Four loading scenarios (lightship, full ballast, crane at maximum outreach, and cargo distribution) were defined, with updated displacement and vertical centre of gravity (KG) values used to recompute hydrostatic parameters (BM, KM, free-surface corrections) and generate full GZ curves. Intact-stability criteria (GM ≥ 0.15 m, area under GZ curve ≥ 0.08 m·rad, angle of vanishing stability ≥ 25°, and GZmax ≥ 0.25 m) were evaluated for each case. Results indicate that the ballast condition yields the highest stiffness (GM ≈ 1.50 m) and energy absorption (AUC ≈ 1.15 m·rad). The crane-outreach scenario represents the narrowest margin (GM ≈ 0.90 m, AUC ≈ 0.60 m·rad). A safe-loading envelope was developed, showing permissible crane loads of up to 100 t at 10 m outreach and limiting lifts beyond 20 m to 50 t or less. Mitigation measures—ballast management, outreach/load restrictions, optimized cargo stowage, and real-time monitoring—are recommended to ensure regulatory compliance and operational safety.